Wallerian degeneration: From mechanism to disease to imaging - Ruiqi Tian; Yingying Zhou; Yuan Ren; Yisen Zhang; Wei Tang (Heliyon)
Wallerian degeneration (WD) was first discovered by Augustus Waller in 1850 in a transection of the glossopharyngeal and hypoglossal nerves in frogs. Initial studies suggested that the formation mechanism of WD is related to the nutrition of neuronal cell bodies to axons. However, with the wide application of transgenic mice in experiments, the latest studies have found that the mechanism of WD is related to axonal degeneration, myelin clearance and extracellular matrix. This review summarizes the discovery and research progress of WD and discusses the mechanism of WD from the perspective of molecular biology. In addition, this review combines the etiology, symptoms and imaging results of WD patients, and analyzes the clinical and imaging characteristics of WD, to provide the best perspective for future clinical research.